CORPUS-BASED ANALYSIS OF HISTORICAL LANGUAGE CHANGE (Ustozlar uchun, 2025)
This article explores how corpus linguistics contributes to the study of historical language change, focusing on how digital corpora reveal patterns of linguistic evolution over time. Corpus-based methods allow researchers to examine authentic texts from different historical periods, tracing changes in vocabulary, grammar, and meaning. Using large, time-structured corpora such as the Helsinki Corpus, the Corpus of Historical American English (COHA), and the ARCHER Corpus, linguists can quantify language development from Old English to Modern English.